Testing in the multivariate general linear model - Kariya, Takeaki (Tokyo, Japan : Kinokuniya Co. ; New York, NY, U.S.A. : Distributed by N.Y. Kinokuniya Bookstores, 1985)
This title provides an integrated introduction to multivariate multiple regression analysis (MMR) and multivariate analysis of variance (MANOVA). It defines the key steps in analyzing linear model data and introduces multivariate linear model analysis as a generalization of the univariate model. Richard F. Haase focuses on multivariate measures of association for four common multivariate test statistics, presents a flexible method for testing hypotheses on models, and emphasizes the multivariate procedures attributable to Wilks, Pillai, Hotelling, and Roy.
Includes index.
Includes bibliographical references: p. 232-242.
aia 08/06/2018
Loans
Keywords: Multivariate analysis; Linear models (Statistics).; Analysis of variance; Statistical hypothesis testing